Lesson planning for middle school physical education meeting the national standards & grade-level outcomes - Doan, Robert John; MacDonald, Lynn Couturier 1959-; Chepko, Stevie; Shape America (Champaign, IL Human Kinetics, 2017)
Lesson Planning for Middle School Physical Education provides lesson plans from experienced middle school physical educators that: will help middle school students meet SHAPE America's National Standards and Grade-Level Outcomes; provide progressive practice tasks and integrate appropriate physical education assessments to evaluate and monitor student progress; make the best use of technology in your physical education classes; include handout materials, homework tasks, lists of needed materials and equipment, questions for student understanding, and reflection questions to ask yourself; and offer guidance on best instructional practices for involving and engaging all students. Lesson Planning for Middle School Physical Education is organized into two parts. Part I addresses important factors in planning for student success, including an introductory chapter that helps you consider the issues that influence student learning and understand the instructional environment and the scope and sequence for K-12 physical education. Part II supplies lesson plans (arranged in modules of eight lessons each) that are based on the Grade-Level Outcomes, offering you a step-by-step guide for building students' skills and knowledge in these areas: Dance and rhythms, Invasion games, Net and wall games, Fielding and striking and target games, Outdoor pursuits, Individual-performance activities, Physical activity participation outside of school, Personal fitness and fitness program design.
Part I Planning for Student Success in the Middle Grades: Chapter 1. The Importance of Teaching for Student Learning in the Middle Grades -- Chapter 2. Teaching to Standards: Planning Middle School Lessons Using the Outcomes -- Chapter 3. Meeting the National Standards and Grade-Level Outcomes in Middle School -- Part II Lesson Plans for Middle School Physical Education: Chapter 4. Applying Students' Skills and Knowledge to Dance and Rhythms -- Chapter 5. Applying Students' Skills and Knowledge to Invasion Games -- Chapter 6. Applying Students' Skills and Knowledge to Net and Wall Games -- Chapter 7. Applying Students' Skills and Knowledge to Fielding and Striking Games and Target Games -- Chapter 8. Applying Students' Skills and Knowledge to Outdoor Pursuits -- Chapter 9. Applying Students' Skills and Knowledge to Individual-Performance Activities -- Chapter 10. Applying Students' Skills and Knowledge to Physical Activity Participation -- Chapter 11. Applying Students' Skills and Knowledge to Program Design and Fitness Assessment
Includes bibliographical references.
Keywords: Physical education and training -- Study and teaching (Middle school) -- United States; Lesson planning -- United States